2009
DOI: 10.1021/jf803975m
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Stability of Thujone, Fenchone, and Pinocamphone in Vintage Preban Absinthe

Abstract: Research was conducted to ascertain whether analyses of vintage absinthe samples represent their original composition in the early 1900s. Absinthe stored in traditional green glass bottles and irradiated with ultraviolet light for up to 200 h exhibited unchanged composition. Samples stored in clear glass exhibited an 18% reduction in beta-thujone content and a concurrent decoloration. These experiments indicate the stability of thujone in vintage absinthes, as these were stored in green glass bottles. The pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 9 publications
2
7
0
Order By: Relevance
“…The average and median concentrations of total thujone in all investigated samples were 27.5 and 22.3 mg/L, correspondingly. These values are in full agreement with our previous findings [7,12,19].…”
Section: Methods Validation and Measurement Of Authentic Samplessupporting
confidence: 93%
See 1 more Smart Citation
“…The average and median concentrations of total thujone in all investigated samples were 27.5 and 22.3 mg/L, correspondingly. These values are in full agreement with our previous findings [7,12,19].…”
Section: Methods Validation and Measurement Of Authentic Samplessupporting
confidence: 93%
“…For the authentic absinthes the RSDs were slightly higher but still acceptably below 10%. Furthermore, NMR results for 69 absinthes were compared with values previously obtained by our conventional LLE-GC/MS method [7,12,19]. Statistical analysis between results from GC/MS and NMR revealed that the linear correlation is significant (P < 0.0001, R = 0.93).…”
Section: Methods Validation and Measurement Of Authentic Samplesmentioning
confidence: 93%
“…The total thujone amount remained constant during the whole experiment (48 hours). This result reconfirmed the stability of thujone under storage conditions 26. Our results showed that rosmarinic acid (in contrast to thujone) is only stable in aqueous tea infusions for approximately five hours (which means that about 15 samples can be prepared and measured in one sequence by NMR).…”
Section: Resultssupporting
confidence: 81%
“…Although this has often been ascribed to the neurotoxicological effects of the thujones (the main constituents of the essential oil of wormwood, Figure 6), it now seems more likely that the excessively-high alcohol content of absinthe and indeed the quality of the alcohol used in some products were responsible. Indeed, it has been shown that the levels of the thujones in actual samples or authentic reformulations of absinthe from this 'preban' period were for the most part within the limits set by current EU legislation [17] . Referring to the case of Vincent van Gogh (1853-1890), an interesting article [18] discusses absinthe and several psychodynamic factors that may have contributed to his psychotic episodes at Arles, when he cut off his ear.…”
Section: Absinthementioning
confidence: 90%